Caerin 1 Antimicrobial Peptides that Inhibit HIV and Neisseria May Spare Protective Lactobacilli - Louise A. Rollins-Smith; Patricia B. Smith; Anna M. Ledeczi; Julia M. Rowe; Laura K. Reinert (MDPI AG, 2020)
Although acquired immunodeficiency syndrome (AIDS) caused by the human immunodeficiency virus (HIV) is a manageable disease for many, it is still a source of significant morbidity and economic hardship for many others. The predominant mode of transmission of HIV/AIDS is sexual intercourse, and measures to reduce transmission are needed. Previously, we showed that caerin 1 antimicrobial peptides (AMPs) originally derived from Australian amphibians inhibited in vitro transmission of HIV at relatively low concentrations and had low toxicity for T cells and an endocervical cell line. The use of AMPs as part of microbicidal formulations would expose the vaginal microbiome to these agents and cause potential harm to protective lactobacilli. Here, we tested the effects of caerin 1 peptides and their analogs on the viability of two species of common vaginal lactobacilli (Lactobacillus rhamnosus and Lactobacillus crispatus). Several candidate peptides had limited toxicity for the lactobacilli at a range of concentrations that would inhibit HIV. Three AMPs were also tested for their ability to inhibit growth of Neisseria lactamica, a close relative of the sexually transmissible Neisseria gonorrhoeae. Neisseria lactamica was significantly more sensitive to the AMPs than the lactobacilli. Thus, several candidate AMPs have the capacity to inhibit HIV and possible N. gonorrhoeae transmission at concentrations that are significantly less harmful to the resident lactobacilli.